2008
DOI: 10.1002/bdra.20515
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of pediatric genetic services to children with birth defects in Texas

Abstract: Although 82% of addresses were within 30 miles of the nearest pediatric genetic clinic, 14% lived 31-100 miles from the nearest facility, and 4% of case families would need to drive more than 100 miles, including some who live in midsized cities, indicating geographic disparities in access to these necessary services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…Our results are congruent with those of Case et al (2008) and Fixler et al (2012) that geographic barriers to access health services can be important. Information on geographic barriers to care may allow program planners, public health officials, and/or health services researchers to target underserved areas and may improve health service delivery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are congruent with those of Case et al (2008) and Fixler et al (2012) that geographic barriers to access health services can be important. Information on geographic barriers to care may allow program planners, public health officials, and/or health services researchers to target underserved areas and may improve health service delivery.…”
Section: Discussionsupporting
confidence: 90%
“…A few studies using birth defects surveillance data have examined location of services and its effect on survival and health service utilization (Case et al, 2008; Cassell et al, 2009; Fixler et al, 2012). Using Texas Birth Defects Registry data for infants born in 1999 to 2004 with major structural defects and chromosomal anomalies, Case et al (2008) found that 14% of those infants were living 31 to 100 miles from a pediatric genetic service provider, and for 4% of these infants, the closest service provider was located more than 100 miles away, due to the limited number of locations providing genetic services. Using North Carolina birth defects and Medicaid data for 1995 to 2002, Cassell et al (2009) found significant geographic differences in the receipt of timely primary cleft surgical repair for children with orofacial clefts.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, researchers evaluated the distance of residential addresses of children born 1999 to 2004 with major and chromosomal birth defects in Texas from pediatric clinical genetic service providers. The authors found disparities in geographic access to services among these children (Case et al, 2008). These studies illustrate that GIS is a convenient and readily available alternative to surveys in identifying geographic barriers to care for children with birth defects, such congenital heart defects and chromosomal defects that require coordinated, specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…Mean, median, ranges, and total travel distance and time were reported. One-way travel distance and time were categorized based on frequency distributions, meaningful cut-points for analyses, and the literature on distance and time to medical care for birth defects and other medical conditions, such as cancer (Kuehn et al, 2007; Case et al, 2008; Huang et al, 2009; Henry et al, 2011; Fixler et al, 2012; Pinto et al, 2012). Travel distance was analyzed in four categories, 0 to 30 miles, 31 to 60 miles, 61 to 90 miles, and greater than 90 miles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation